Radiopharmaceuticals for diagnosis in nuclear medicine: a short review - Payolla, Filipe Boccato; Massabni, Antonio Carlos; Orvig, Chris (Eclética Química, 2019)
Radiopharmaceuticals are radioactive compounds which have a bound radionuclide in their structure, whose purpose is directing the radionuclide to a location to be treated or to obtain images. Nuclear medicine is the medical specialty that employs radiopharmaceuticals, which has presented itself as a tremendously useful ally for medicine assisting in various diagnoses and treatments, especially for cancer. The general objective of this work is to identify the main radionuclides and metal complexes currently used as radiopharmaceuticals. The main metal complexes used as radiopharmaceuticals are compounds of technetium (99mTc) like sodium pertechnetate and methylenediphosphonate MDP-99mTc and other compounds of indium (111In), thallium (201Tl), gallium (67Ga, 68Ga), iodine (123I and 131I), chromium (51Cr), sulphur (35S), phosphorus (32P), fluorine (as fluorodeoxyglucose, 18F-FDG and sodium fluorine, Na18F), which are widely used in the nuclear medicine for diagnosis by imaging. They have been of great importance for the early diagnosis of numerous diseases, mainly cancer. Currently, technetium compounds are the majority of radiopharmaceuticals used in all countries. In Brazil, Institute of Energy and Nuclear Research (IPEN) is one of the most important distributors of radiopharmaceuticals, producing, importing and distributing them to clinics and hospitals over the country.